ANALYSIS OF THE EFFICIENCY AND EFFECTIVENESS OF REGIONAL FINANCIAL MANAGEMENT IN THE CITY OF BIMA - Gilang Sakti Pradana; Puja Purnama; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
This study aims to analyze the level of effectiveness and efficiency of regional finance in the City of Bima. The data used is secondary data, namely the Bima City APBD data for the 2016-2020 budget period. This study aims to calculate the level of effectiveness and efficiency of the regional finances of the City of Bima whether regional revenues and expenditures at the Regional Revenue Service of the City of Bima have been carried out efficiently and effectively. The analysis technique used is to calculate the Regional Financial Efficiency Ratio and Effectiveness Ratio. The results obtained show that overall, the average regional financial effectiveness ratio for the City of Bima for the 2016-2020 period has reached an effective level. It can be concluded that the Bima City government has succeeded in realizing Regional Original Income (PAD) from the estimated target so that the potential of existing PAD can be maximized by the local government to support the development of Bima City. Meanwhile, overall, the average regional financial efficiency ratio for the City of Bima during the 2016-2020 fiscal year was stated to be less efficient because regional expenditures were still high when compared to total regional revenues